2021
DOI: 10.1080/09540105.2021.1982870
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-inflammatory activity of walnut protein derived peptide leucine-proline-phenylalanine in lipopolysaccharides-irritated RAW264.7 cells

Abstract: The purpose of this study was to explore the anti-inflammatory mechanism of walnut peptide LPF in the LPS-induced RAW264.7 cells model. The walnut peptide LPF down-regulated the phagocytic ability and the production of nitric oxide (NO) induced by LPS-stimulated RAW264.7. Molecular docking analysis showed that the walnut peptide LPF can bind into the active pocket of inducible nitric oxide synthase (iNOS) with high affinity. Further, the mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…WPs LPF also reduced iNOS, cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) mRNA expression. The decrease of IκB-α mRNA expression indicated that the anti-inflammatory effect of WPs LPF was related to the NF-κB signal pathway . Asp, Phe, Glu, and Leu residue in WPs might contribute to anti-inflammatory activity .…”
Section: Bioactivity Of Walnut Protein Hydrolysatesmentioning
confidence: 97%
See 1 more Smart Citation
“…WPs LPF also reduced iNOS, cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) mRNA expression. The decrease of IκB-α mRNA expression indicated that the anti-inflammatory effect of WPs LPF was related to the NF-κB signal pathway . Asp, Phe, Glu, and Leu residue in WPs might contribute to anti-inflammatory activity .…”
Section: Bioactivity Of Walnut Protein Hydrolysatesmentioning
confidence: 97%
“…The decrease of IκB-α mRNA expression indicated that the anti-inflammatory effect of WPs LPF was related to the NF-κB signal pathway. 103 Asp, Phe, Glu, and Leu residue in WPs might contribute to anti-inflammatory activity. 103 As shown in Figure 4D, the main anti-inflammatory mechanisms of WPs include reducing the content of anti-inflammatory factors, inhibiting the production of ROS, and the decomposition of the mitochondrial membrane potential (MMP).…”
Section: Bioactivity Of Walnut Protein Hydrolysatesmentioning
confidence: 99%
“…Peptides with hydrophobic amino acids that are present at the N-terminus tend to have strong anti-inflammatory activity. These include the walnut tripeptide LPF [ 42 ]; the oligopeptide IALLIPF obtained from millet [ 31 ]; the corn oligopeptides LTDPAAS, LPVGPQ and LLPSSQ [ 30 ]; and the hemp seed oligopeptides WVSPLAGRT and IGFLIIWV [ 40 ]. The hydrophobic amino acids at the N-terminus of the peptide chain confer excellent anti-inflammatory effects on peptides, which reduce inflammation by inhibiting the cascade responses of key inflammatory signaling pathways and the expression of downstream inflammatory factors.…”
Section: Factors Affecting the Anti-inflammatory Effects Of Plant-der...mentioning
confidence: 99%
“…Therefore, neurodegenerative diseases can be alleviated by blocking signaling between peripheral cells and the central nervous system [ 35 ]. Wang et al reported a low molecular weight peptide, leucine–proline–phenylalanine (LPF), isolated from walnut protein hydrolysates, which attenuated memory impairment by reducing neuroinflammation and oxidative stress in the brain tissue of mice induced by intraperitoneal injection of LPS, and this was also associated with the suppression of iNOS, COX-2, and TNF-α mRNA expression in macrophages [ 36 ]. The rat pheochromocytoma cell line PC12 with a morphology and physiological function similar to neurons is a well-established cell model for studying the cellular biology of neurons [ 37 ].…”
Section: Studies Of the Inhibitory Effects Of Walnuts On Neuroinflamm...mentioning
confidence: 99%
“…It was found that LPS-induced macrophages stimulated the activation of microglia, indicating that macrophage-mediated peripheral inflammation may accelerate neuroinflammation [ 34 ]. Wang et al showed that the walnut peptide leucine–proline–phenylalanine downregulated the mRNA expression of inflammatory mediators, such as INOS, COX-2, and TNF-α, in LPS-treated RAW264.7 macrophage cells, suggesting the potential of walnut peptides against neuroinflammation through regulation of peripheral immune cells [ 36 ].…”
Section: Anti-inflammatory Components Of Walnutsmentioning
confidence: 99%